Doctrinal Criticism of BRIN Museum Bogor City - Wahyu Buana Putra; Abdul Ihsan Supriatna (Talenta Publisher, 2024)
This research is a critique of the architecture of the BRIN museum using the doctrinal critique method. Museums are places to preserve and protect historical objects. The BRIN Museum in Bogor City is intended as a facility related to archaeology and human natural history. In addition, there are also supporting facilities that aim to generate income. The design of the BRIN Museum implements the form of artifact buildings in Indonesia. In order to make the visual appearance of the BRIN museum building design more attractive through a transformation planning approach that follows the shape of Borobudur Temple. The goal is to preserve the cultural elements in Indonesia and make the architect's work more modern and new through the Neo Vernacular approach by carrying out traditional themes that are applied in a more modern way by adjusting the current era. Each floor of the museum building is made of stepped pundens derived from the philosophy of Borobudur Temple. Generally, BRIN museum buildings apply the form follows function theory, which maximizes the function of the building to achieve aesthetic value. This is done so that each space can function optimally. This research uses a descriptive qualitative method. Data collection techniques were carried out using primary and secondary data.